Rotas de processo para minérios goethíticos - Aloisio Sa Cabral (2010)
The proposed study aimed at developing a process route to process an iron ore body with 14 years of predicted operation. The enterprise, belonging to VALE, is located in Minas Gerais, at approximately 40km southeast from Belo Horizonte, occupying 1,600 ha in the municipalities Rio Acima, Raposos, Caeté, and Santa Bárbara. The ore body was designated as rich and contains the minerals hematite, magnetite, martitic hematite, and goethite. Specific methodologies were adopted to each project phase: mineralogical characterization, laboratory scale experiments, and pilot scale tests. The results from the mineralogical characterization indicated the presence in the deposit of hydrated minerals, martitic hematite being the predominant iron bearing species,presenting particles in a martitization process with significant participation of magnetite. The adopted crushing flowsheet included primary, secondary, and tertiary stages. The crushing product is in the size range passing 38.0mm. The concentrator process routestarted with double stage screening at 8.0mm and 1.0mm, a quaternary crushing circuit, a double hydrocyclones classification circuit followed by spiral classifiers. The fractions -8.0+1.0mm and -1.0 + 0.15mm did not require concentration and were combined as sinter feed. Due to the magnetite presence, a low intensity magnetic separation circuit is required, as protection for the high intensity magnetic circuit. The use of a triple desliming stage with optional NaOH injection was necessary. A conventional flotation circuit with rougher, cleaner, double scavenger stages was selected. Conventional thickeners were adopted for slimes and concentrate. Belt filters were chosen for the sinter feed from the magnetic concentration and disc filters for the pellet feed. The final result was 24Mta of product consisting of 72% sinter feed and 28% pellet feed.